Comparison between RCC-MR and ASME section-III/NH for creep-fatigue design of bellows. (2018) - Krovvidi, S.C.S.P. Kumar; Bhaduri, A.K.
High temperature design of the bellows for nuclear applications must comply with validated design codes such as ASME section-III or RCC-MR. The geometry of the bellows preliminarily arrived as per EJMA is analysed using finite element analysis. High temperature design of the bellows as per ASME section-III/subsection-NH and RCC-MR is carried out for various loading conditions. It is observed that the design methodology given in ASME section-III/NH underestimates when low/no primary stress is present as this method does not take into account the relaxation of the pure secondary stresses even with longer hold times. The method given in RCC-MR addresses relaxation of secondary stresses with time even at low/zero primary stresses and hence, RCC-MR is considered among the two codes for design of bellows operating at high temperature. Further, cycle life testing at 823 K also has been carried out and found that the life predicted by the method given in RCC-MR is conservative.